These squatters are not innocent: the evidence of parasitism in sponge-inhabiting shrimps - Ďuriš, Zdeněk; Horká, Ivona; Juračka, Petr Jan; Petrusek, Adam; Sandford, Floyd (PloS one, 2011)
Marine sponges are frequently inhabited by a wide range of associated invertebrates, including caridean shrimps. Symbiotic shrimps are often considered to be commensals; however, in most cases, the relationship with sponge hosts remains unclear. Here we demonstrate that sponge-inhabiting shrimps are often parasites adapted to consumption of sponge tissues. First, we provide detailed examination of morphology and stomach contents of Typton carneus (Decapoda: Palaemonidae: Pontoniinae), a West Atlantic tropical shrimp living in fire sponges of the genus Tedania. Remarkable shear-like claws of T. carneus show evidence of intensive shearing, likely the result of crushing siliceous sponge spicules. Examination of stomach contents revealed that the host sponge tissue is a major source of food for T. carneus. A parasitic mode of life is also reflected in adaptations of mouth appendages, in the reproduction strategy, and in apparent sequestration of host pigments by shrimp. Consistent results were obtained also for congeneric species T. distinctus (Western Atlantic) and T. spongicola (Mediterranean). The distribution of shrimps among sponge hosts (mostly solitary individuals or heterosexual pairs) suggests that Typton shrimps actively prevent colonisation of their sponge by additional conspecifics, thus protecting their resource and reducing the damage to the hosts. We also demonstrate feeding on host tissues by sponge-associated shrimps of the genera Onycocaris, Periclimenaeus, and Thaumastocaris (Pontoniinae) and Synalpheus (Alpheidae). The parasitic mode of life appears to be widely distributed among sponge-inhabiting shrimps. However, it is possible that under some circumstances, the shrimps provide a service to the host sponge by preventing a penetration by potentially more damaging associated animals. The overall nature of interspecific shrimp-sponge relationships thus warrants further investigation.
Keywords: Animals; Porifera; stravovací zvyklosti; Phylogeny; symbióza; zvířata; biologická evoluce; Biological Evolution; Host-Parasite Interactions; fylogeneze; Decapoda (Crustacea); interakce hostitele a parazita; fyziologická adaptace; Decapoda; Feeding Behavior; Symbiosis; Adaptation, Physiological